Synthesis of Reovirus Oligo Adenylic Acid In Vivo and In Vitro - Silverstein, Samuel C. (1974)
The formation of reovirus double-stranded (ds) RNA and of oligo adenylic acid (oligo A) is inhibited by 5 μg of actinomycin D per ml added at the time of viral infection. Viral proteins are synthesized and assembled into dsRNA-deficient particles under these conditions. The addition of cycloheximide to infected cells during the mid-logarithmic phase of viral replication terminates protein and dsRNA synthesis, but allows continued oligo A synthesis for about 1 h. The (3)H-labeled oligo A formed in the presence of cycloheximide is incorporated into particles whose density in CsCl is identical to that of reovirions. Using the large particulate or virus factory-containing cytoplasmic fraction of infected L-cells, we have established an in vitro system for the synthesis of oligo A. The in vitro product migrates slightly faster in sodium dodecyl sulfate acrylamide gels than marker oligo A. Oligo A synthesis in vitro continues for about 1 h, requires, the presence of only one ribonucleoside triphosphate (ATP), is not inhibited by DNase or RNase, but is abruptly terminated by the addition of chymotrypsin to the reaction mixture. Oligo A formed both in vivo and in vitro is released from the factory fraction by chymotrypsin digestion. The enzymes which catalyze the synthesis of oligo A, dsRNA, and single-stranded RNA all exhibit a similar temperature dependence with an optimum of ∼45 C. These results indicate that oligo A is formed within the core of the nascent virion after the completion of dsRNA synthesis; they suggest that the oligo A polymerase is an alternative activity of the virion-bound transcriptase and that it is regulated by outer capsomere proteins.